Isolation and in vitro antidiabetic properties of a proanthocyanidin from Cinnamomum zeylanicum - Taher, M. (2005)
Characterization and in vitro testing of antihyperglycemic activity of a natural product from the stem bark of Cinnamomum zeylanicum have been carried out. Characterization was carried out using HPLC, ultraviolet, infrared, 1H and 13C nuclear magnetic resonance spectroscopy and mass spectrometry. Based on the spectroscopics data, bioactive compound was identified as cinnamtannin B1. Cinnamtannin B1 is a double linked flavan-3-ol trimer known as A-type proanthocyanidin. Its activity was evaluated using cell proliferation, cell differentiation, glucose regulation and phosphorylation of insulin receptor -subunit in 3T3-L1 cells. Cinnamtannin B1 promoted cell proliferation approximately 2-fold at 48 hours after treatment. Dosage range of cinnamtannin B1 in promoting cell proliferation was 100-150 g/mL (0.11-0.17 mM). A mixture of 0.1 mM cinnamtannin B1 and 150-200 g/mL water extract induced differentiation of adipocytes similar to that of the insulin activity. Addition of cinnamtannin B1 into the culture of 3T3-L1 adipocyte increased glucose consumption up to 32%. The mixture of 0.1 mM cinnamtannin B1 and 100 nM insulin stimulated glucose uptake from a basal value by 1.8 and 1.7-fold, respectively. Cinnamtannin B1 and water extract stimulated phosphorylation of insulin receptor -subunit. There was no phosphorylation of insulin receptor observed in 3T3-L1 preadipocytes. The activity of cinnamtannin B1 in stimulating glucose uptake and phosphorylation were inhibited by wortmannin and cytochalasin B. In contrast, sodium orthovanadate stimulated glucose uptake and phosphorylation. The results demonstrated that activity of cinnamtannin B1 and water extract mimics insulin action. They acted directly on insulin receptor -subunit by activation of PI3-kinase that stimulates glucose transporter-4 (GLUT-4) translocation. Stimulation of GLUT4 translocation therefore stimulates glucose uptake lead to glucose disposal process in adipocytes. Based on the work that has been carried out, it was suggested that cinnamtannin B1 could be one of the potential lead drug compound in the treatment of type 2 diabetes.